2012
DOI: 10.1111/j.1444-0938.2011.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Tear osmolarity in unilateral pseudoexfoliation syndrome

Abstract: Purpose:The aim was to evaluate tear osmolarity of patients with clinically unilateral pseudoexfoliation (PEX) syndrome and to compare the values with otherwise normal subjects. Methods: Sixty-two eyes of 31 patients with unilateral PEX syndrome and 31 eyes of 31 normal subjects were studied. The TearLab osmolarity system (OcuSense, Inc, San Diego, CA, USA) was used to measure tear osmolarity. Eyes were grouped as normal eyes of patients having unilateral PEX syndrome (group A), eyes of patients having unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
3
21
0
1
Order By: Relevance
“…As tear osmolarity is now considered as the key pathogenic factor causing ocular surface inflammation, symptoms and tissue damage, they concluded that patients with PEX syndrome could be more prone to the development of dry eye syndrome. 25 We also found the similar results in this study. Our results showed us that there was a statistically significant difference between PEX (À) and PEX syndrome groups in the mean of Schirmer and TBUT tests.…”
Section: Discussionsupporting
confidence: 90%
“…As tear osmolarity is now considered as the key pathogenic factor causing ocular surface inflammation, symptoms and tissue damage, they concluded that patients with PEX syndrome could be more prone to the development of dry eye syndrome. 25 We also found the similar results in this study. Our results showed us that there was a statistically significant difference between PEX (À) and PEX syndrome groups in the mean of Schirmer and TBUT tests.…”
Section: Discussionsupporting
confidence: 90%
“…Oncel et al established that tear film osmolarity was higher in patients with PEX, which can be explained by the dysfunction of the goblet conjunctival cells (10). TBUT test results from our study recorded lower in patients with PEX (XFS/XFG) compared with control group patients with statistically significant difference.…”
Section: Discussionsupporting
confidence: 38%
“…For instance, eyes with pseudoexfoliation syndrome, a condition that is thought to alter goblet cell activity and mucin production, have been reported to have increased tear osmolarity when compared to a control group. 38 Patients with pterygia, a predominantly inflammatory condition, also show increased tear osmolarity when compared with a control group. 39 Keratoconus has been demonstrated to reduce corneal sensitivity, but tear osmolarity was similar to a control group.…”
Section: Resultsmentioning
confidence: 99%